Internet-based workplace communications industry & academic applications - St. Amant, Kirk, 1970-; Zemliansky, Pavel; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
The essays in this collection advance the project of articulating online workplaces as real and significant, as complex networks of relations that we need to take seriously. The emergent culture of networked communication poses many interesting challenges for researchers, teachers, and writers. In an emergent culture, even the terminologies we use to identify the subject are contested, making it difficult to agree on what we're writing about in the first place, not to mention our reasons for studying it or how we might best meet the challenges it poses.
Section VI: Future Trends in Computer Use for Written Communication -- 12. Telework : a guide to professional communication practices -- 13. Open source primer -- 14. Cut and paste : remixing composition pedagogy for online workspaces -- About the Editors -- About the Authors -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: English language -- Business English -- Study and teaching (Higher) -- Computer network resources; English language -- Rhetoric -- Study and teaching -- Computer network resources; Business communication -- Computer-assisted instruction; Business communication -- Computer network resources; Business writing -- Computer-assisted instruction; Business writing -- Study and teaching (Higher); Internet in education; Electronic books